2014
DOI: 10.18806/tesl.v31i1.1164
|View full text |Cite
|
Sign up to set email alerts
|

Career Development and Professional Attrition of Novice ESL Teachers of Adults

Abstract: Research and development in language teacher education and, more recently, teacher accreditation has had enormous impact on the professional lives of ESL teachers in Canada. There has been less interest, however, in examining the ca- reer development and employment experiences of accredited ESL teachers as they transition from TESL programs to ESL classrooms. In this article, we report on a study examining this issue for ESL teachers of adults in Ontario, in which 147 ESL teachers responded to a survey and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…They found that on a scale of 1 to 10, the mean response was 7, without significant variation across programs. Survey data with teachers of ESL to adults, however, have shown enormous variation in working contexts and conditions, including full-time unionized positions and part-time contract positions (see Haque and Cray 2007, Valeo 2013, Valeo and Faez 2013). Thus, not only the number of years of teaching experience, but also teaching context and training are significant factors in levels of teacher confidence and comfort with the CLB.…”
Section: A Framework For Instructionmentioning
confidence: 99%
“…They found that on a scale of 1 to 10, the mean response was 7, without significant variation across programs. Survey data with teachers of ESL to adults, however, have shown enormous variation in working contexts and conditions, including full-time unionized positions and part-time contract positions (see Haque and Cray 2007, Valeo 2013, Valeo and Faez 2013). Thus, not only the number of years of teaching experience, but also teaching context and training are significant factors in levels of teacher confidence and comfort with the CLB.…”
Section: A Framework For Instructionmentioning
confidence: 99%
“…A follow‐up study by Valeo and Faez () includes interview data that give voice to experiences of job insecurity and attrition. As one respondent noted, “It's very difficult to stay, to first get the position, and then to stay in that position for a long time because of all this uncertain budget and funding” (Valeo & Faez, , p. 13). Other respondents spoke of the need to have “two or more part‐time jobs on a daily basis to survive” and the “stress of working in short three‐week assignments at various places” (p. 13).…”
Section: Policy and Certification Transitions At Tesl Ontariomentioning
confidence: 99%
“…Yet, for TESL Ontario, or any other TESOL organization, there is something profoundly ideological and deeply troubling when advocacy is conflated with professional development. In terms of LTI, advocacy takes on neoliberal overtones, as subjects are required to become increasingly entrepreneurial and inward‐looking, driven to identify and compensate for “gaps” in their own skill set, ever mindful of the terrors of performativity (Ball, ; Clarke, ) they must negotiate in times of intensified job precarity (Valeo & Faez, ). Considering the emotional and material investments required, it is an irrational, anxiety‐ridden notion of advocacy on offer, one potentially characterized as cruel optimism (Berlant, ), “the fantasy of meritocracy, a fantasy of being deserving … about so many bad jobs contingently available to so many contingent workers and never enough money, never enough love, and barely any rest, yet with ruthless fantasy abounding” (p. 167).…”
Section: Policy and Certification Transitions At Tesl Ontariomentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability of the profession, lack of a defined teacher career path, and poor working conditions have been documented in private, government-sponsored, and postsecondary English teaching contexts (Breshears, 2004(Breshears, , 2008MacPherson, Kouritzin, & Kim, 2005;Shaw, 2014;Smithwick, 2014;Valeo & Faez, 2014). Although seen by some as offering comparatively better working conditions, the university environment is not without its own unique challenges to English teachers' professionalism.…”
mentioning
confidence: 99%